Colombia : Land Policy in Transition - World Bank (Washington, DC, 2013)
Unequal land distribution and the negative social and economic implications resulting from such polarization in Colombia have long been of concern to policymakers. A 1950 World Bank mission identified unequal land distribution as a key impediment to economic and social development in the country. Since then, a wide range of policies has been adopted to deal with this issue and its consequences. Numerous studies show that the success of these policies was often limited by a combination of an inappropriate policy environment, limited financial resources, cumbersome processes loaded with bureaucratic obstacles, drug money, and violence. This report uses new empirical evidence to describe the dimensions and impact of the problem of land access and land distribution and past policies to deal with this issue, and to identify possible avenues to address land issues in an integrated manner in future interventions. It complements contemporaneous studies by the Bank on rural finance and agricultural competitiveness,' and past and ongoing work on Afro-Colombian land issues in the Pacific Coast and improved land access for the indigenous population. Among the issues discusses are the role of land in confronting the challenges of transition in Colombia's rural sector, the extent and consequences of land inequality, the role of land policy in dealing with involuntary displacement, the use of land markets to facilitate productivity-enhancing land transfers to small producers, improving land access and productivity through redistributive land reform, and improving agricultural competitiveness in a way that benefits the poor.